Resistance Exercise Influence on Diabeticum Neuropathy Improvement in Type 2 DM Patients - Ratna Yunita Sari; Imamatul Faizah (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Diabetic neuropathy is a microvascular complication of diabetes mellitus that attacks the peripheral parts and causes nerve damage. One effort to improve the complications of diabetes mellitus is to apply exercise. The exercise that can be carried out is resistance exercise which is a modality therapy in the implementation of type 2 diabetes mellitus which is expected to control blood sugar levels and facilitate peripheral tissue circulation to improve diabetic neuropathy. The purpose of this study was to determine the effect of resistance exercise on the improvement of diabetic neuropathy in patients with type 2 diabetes mellitus. The study design was a quasi-experiment with the untreated control group design with dependent pre-test and post-test samples. The probability sampling technique is a type of random sampling that meets the inclusion and exclusion criteria with a sample size of 120 respondents. The instrument used to measure diabetic neuropathy uses a modified MNSI (Michigan Neuropathy Screening Instrument) and MDNS (Michigan Diabetic Neuropathy Score). Statistical tests using Paired Sample t-Test and Independent t-Test with a significant p <0.05. The results showed a mean improvement in diabetic neuropathy in the intervention group 8.37 and the control group 17.48. Data analysis showed that resistance exercise affected the improvement of diabetic neuropathy with p = 0.00. Resistance exercise that is routinely done can reduce neuropathy scores so that there is an improvement in diabetic neuropathy in people with type 2 diabetes mellitus.